Guide to mitigation options to reduce greenhouse gas emissions in Chinese dairy sector - Sha, Wei; Zijlstra, Jelle; Wang, Yue; Hongmin, Dong (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Livestock emissions from dairy farms contribute to global warming. To mitigate this impact, dairy farms can consider and implement mitigation options. The objective of this report is to give an overview of mitigation options that can be applied on large scale Chinese dairy farms to reduce the emission of the greenhouse gases methane, nitrous oxide and carbon dioxide. This report is expected to support researchers, farm advisors, policy advisors, farm managers and dairy chain stakeholders to become informed about the characteristics of mitigation options and their potential to contribute to the reduction of greenhouse gas emissions from dairy farms. The report contains descriptions of 27 mitigation options divided into seven main domains in the reduction of greenhouse gases on dairy farms. The first group of options is about herd management and deals with animal health, idle cows, raising young stock, age at first calving, transition period and genetic selection. The second group is about crop production and contains options about fertilization and crop yields. The third domain is feeding and feed management that describes options on precision feeding, adjusted diets, feed additives and providing water. Domain number four is about stable characteristics: cooling against heat stress, manure collection and open-air playgrounds for cattle. The fifth group is about manure management containing mitigation options on manure storage, cover lagoon, acidification, anaerobic digestion, composting and manure application. Group six focuses on energy management: saving energy and the production of renewable energy. The seventh and last domain is carbon sequestration in soils. For each of the mitigation options we have strived to provide information about these aspects: technical principles, technical considerations relevant to implementation, advantages and disadvantages, mitigation potential and references. All this collected information is presented in a separate paragraph for each mitigation option. These paragraphs can be seen as factsheets that can be read independently from each other.